Study of Ontology-Based Swine Diagnosis Technology - Yun-peng CUI; Xiao-lu SU; Shi-hong LIU (Journal of Integrative Agriculture, 2012)
The computer swine disease diagnosis is an important tool for swine farming industry, but the traditional expert system cannot meet the requirement of practical application. To improve the situation, a swine disease ontology is constructed, which can model the knowledge of swine disease diagnosis into a concept system, and a mechanism that can save the ontology into relational database is established, further more a computer system is developed to implement ontology-based swine disease diagnosis, so make the diagnosis results extended and more precise.